Pesquisa e análise dos protocolos de segurança nas implementações de redes utilizando o padrão IEEE 802.11 - Silva Neto, Eduardo Santana da (2011)
This paper has its main subject the safety in wireless network. Stipulate the safety methods in a wireless network, comparing the protocols WEP, WPA e WPA2 is the focus of this paper. The research is applied and explanatory, as its purpose, using bibliographic support and a field research to collect information about the points of access in a great company. From this collect, along with the bibliographic support, we expect to define the criteria to configure a wireless network, making possible to apply these criteria in every point of access existent or those which will be configured.